2011
DOI: 10.1080/10476210.2010.520699
|View full text |Cite
|
Sign up to set email alerts
|

Emphasizing collaborative practices in learning to teach: coteaching and cogenerative dialogue in a field‐based methods course

Abstract: This manuscript details a field-based methods course for preservice teachers that has been designed to integrate shared teaching experiences in elementary classrooms with ongoing critical dialogues with a focus on highlighting the complexities of teaching. I describe the structure of the course and explore the use of coteaching and cogenerative dialogue as approaches to learning how to teach. Vignettes that typify experiences in this course are analyzed, and two main findings explored. First, coteaching provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…A study by Siry (2011) demonstrated another feature of PAR: the continuous shaping and reshaping of the participants' roles as they engaged in cogen and coteaching. Siry conducted a study with six preservice teachers and 25 children in third grade with their science teacher.…”
Section: Integrating Cogen In Parmentioning
confidence: 99%
“…A study by Siry (2011) demonstrated another feature of PAR: the continuous shaping and reshaping of the participants' roles as they engaged in cogen and coteaching. Siry conducted a study with six preservice teachers and 25 children in third grade with their science teacher.…”
Section: Integrating Cogen In Parmentioning
confidence: 99%
“…Several studies have reported on implementing Roth and Tobin's (2002) model of co-teaching (Salles El Kadri & Roth, 2013;Siry & Lang, 2010;Siry, 2011). For example, Siry (2011) explains that while collaborative teaching practices allow novices to engage in the actual activities of teaching at the elbow of more expert educators, co-generative dialogues facilitate the co-teachers' reflections on their shared experiences in the classroom and their deconstruction and planning of alternative instructional activities designed to maximize student learning in the future. Siry (2011) also found that by the end of the teaching practicum the novices were particularly appreciative of the support received from more than one teacher as they co-taught their lessons.…”
Section: Teacher Mentoringmentioning
confidence: 99%
“…Teacher mentoring is an important issue in much recent research in the context of general teacher education (Bradbury, 2010;Orland-Barak, 2010;Siry, 2011;Wang & Odell, 2007). A number of early research studies on teacher mentoring clearly show that a mentor can play an important role in the development of a pre-service teacher's teaching expertise during a field-based practicum experience (Guyton & McIntyre, 1990).…”
Section: Teacher Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the specific field of science education, co-teaching has been suggested as a way to improve instructional practices among preservice (Siry 2011) and practicing (Martin and Scantlebury 2009) teachers. While co-planning again has been viewed as an important aspect of these co-teaching relationships (see Tobin, Roth and Zimmermann 2001, for heuristic), the process has not been examined in detail.…”
mentioning
confidence: 99%